Bipolar spectrum disorders are associated with increased gray matter volume in the medial orbitofrontal cortex and nucleus accumbens. Issue 1 (8th March 2022) - Damme, Katherine S. F.; Alloy, Lauren B.; Kelley, Nicholas J.; Carroll, Ann; Young, Christina B.; Chein, Jason; Ng, Tommy H.; Titone, Madison K.; Bart, Corinne P.; Nusslock, Robin
Abstract: Objective: Elevated sensitivity to rewards prospectively predicts Bipolar Spectrum Disorder (BSD) onset; however, it is unclear whether volumetric abnormalities also reflect BSD risk. BSDs emerge when critical neurodevelopment in frontal and striatal regions occurs in sex‐specific ways. The current paper examined the volume of frontal and striatal brain regions in both individuals with and at risk for a BSD with exploratory analyses examining sex‐specificity. Methods: One hundred fourteen medication‐free individuals ages 18–27 at low‐risk for BSD (moderate‐reward sensitivity; N = 37), at high‐risk without a BSD (high‐reward sensitivity; N = 47), or with a BSD ( N = 30) completed a structural MRI scan of the brain. We examined group differences in gray matter volume in a priori medial orbitofrontal cortex (mOFC) and nucleus accumbens (NAcc) regions‐of‐interest. Results: The BSD group had enlarged frontostriatal volumes (mOFC, NAcc) compared to low individuals ( d = 1.01). The mOFC volume in BSD was larger than low‐risk ( d = 1.01) and the high‐risk groups ( d = 0.74). This effect was driven by males with a BSD, who showed an enlarged mOFC compared to low ( d = 1.01) and high‐risk males ( d = 0.74). Males with a BSD also showed a greater NAcc volume compared to males at low‐risk ( d = 0.49), but not high‐risk males. Conclusions: An enlarged frontostriatal volume (averaged mOFC, NAcc) is associated with the presence of a BSD, while subvolumes (mOFC vs. NAcc) showed unique patterning in relation to risk. We report preliminary evidence that sex moderates frontostriatal volume in BSD, highlighting the need for larger longitudinal risk studies examining the role of sex‐specific neurodevelopmental trajectories in emerging BSDs. Abstract : Enlarged volume in the mOFC may be associated with BSD disease processes in males, whereas enlarged NAcc volume may reflect a marker of risk for BSD in males. These findings emphasize the potential role of sex and neurodevelopment in the risk for a BSD. Additionally, these findings highlight the need for larger longitudinal risk studies examining the role of sex‐specific neurodevelopmental trajectories in emerging BSDs.